Auditory outcomes and predictors following ossiculoplasty in cholesteatoma surgery: a retrospective analysis - Karkas, Alexandre; Tinquaut, Fabien; Asimakopoulos, Asimakis; Grondier, Brandon; Bertholon, Pierre; Abounaidane, Ines (Frontiers in Surgery, 2025)
IntroductionMiddle ear cholesteatoma causes bone/ossicular erosion. This study aimed to analyze auditory outcomes after ossiculoplasty in cholesteatoma surgery and to identify predictors of hearing outcomes related to middle ear or surgery.MethodsA retrospective study was conducted on patients who underwent ossiculoplasty during cholesteatoma surgery (2019–2024). Preoperative, short-term (2-month), and midterm (8-month) postoperative audiograms were analyzed. Potential pre-/postoperative parameters influencing hearing were sought.ResultsEighty-eight cases were included (20 pediatric, 68 adult). There were 56 primary surgeries, and 28 patients had preoperative cholesteatoma complications. In case of present stapes, a stapes–cartilage augmentation was mostly performed, followed by a partial ossicular replacement prosthesis. In case of absent stapes, a total ossicular replacement prosthesis was used. There were 10 postoperative complications (1 prosthesis extrusion) and 16 residual cholesteatomas (1–3 years). Short-term mean postoperative gain in bone conduction (ΔBC) was 0.3 dB, while midterm ΔBC was 1.4 dB. Short-term mean postoperative gain in air conduction (ΔAC) was 3.4 dB, while midterm ΔAC was 4.5 dB. Short-term mean postoperative gain in air–bone gap (ΔABG) was 3.4 dB, while midterm ΔABG was 3.7 dB. Preoperatively, younger age favorably influenced AC and BC, and the presence of stapes favorably influenced ABG. Postoperatively, regarding midterm ΔABG, the absence of posterior tympanotomy was a predictor of good hearing outcome. Considering the midterm postoperative ABG alone, the absence of mastoidectomy was a favorable predictive factor. Regarding midterm ΔAC, primary surgery was a predictor of a good hearing outcome. Considering postoperative AC alone, there were three favorable predictive factors, namely, younger age, primary surgery, and absence of mastoidectomy. There was no predictive factor for midterm ΔBC. The malleus handle had no effect on auditory results.DiscussionPostoperative auditory results of our study are fair, given the preoperative aggressiveness/extension of cholesteatoma, but were comparable to a few other studies, as were the rates of postoperative complications and residual disease. Younger age and presence of stapes were predictive of better preoperative hearing. Postoperatively, younger age, absence of mastoidectomy, absence of posterior tympanotomy, and primary surgery were predictors of good hearing outcome. Results in the literature are highly variable, sometimes contradictory. This stems from the diversity of disease extension, surgical techniques, and materials used in ossiculoplasty.